PROSPECTS FOR THE WORLD MARINE FISHERY PRODUCTION - Paiva, Melquíades Pinto; Fonteles-Filho, Antônio Adauto; de Melo, José Sávio Colares; Silva, Sinfrônio Sousa (Arquivos de Ciências do Mar, 2018)
In this paper the authors shall be concerned with attempting to find out the year when the most likely of those estimates will be reached, and what will be the composition of the catches by oceans and their regions, as well as by groups of species.